A study of the thermodynamic properties of poly [2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] at infinite dilution using inverse gas chromatography - Kaya, Ismet; Demirelli, Kadir (My University, 1999)
Some thermodynamic quantities were obtained for the interactions of poly [2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] with alcohols, ketones, acetates, aromatics and alkanes by inverse gas chromatography in the temperature range 160-200° C. The specific retention volumes, Vog , weight fraction activity coefficients of solute probes at infinite dilution, ??1, Flory-Huggins thermodynamic interaction parameters, ??12 between polymer and solvents were determined. The partial molar free energy, ???1 , the partial molar heat of mixing, ? H?1 at infinite dilution and the solubility parameters of the polymer, ?2 were calculated.
Keywords: Inverse gas chromatography; Poly [2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate]; Polymer-solvent interactions